Rancang Bangun Aplikasi Pengelolaan Persediaan Pada Planktoon Garage Store - Umair Mustaurid Arridho; Vivine Nurcahyawati; Martinus Sony Erstiawan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Abstract : PLANKTOON GARAGE STORE is Engaged in Manufacturing Sector.  The weakness at the company's sales system is that, the company difficult to determine the increase in the item goods and know all recording reservations and sales transactions that have been done, in the absence of reports that provide information about it. Other problems are also affecting the company is , the production department does not know how many items are to be produced so that the warehouse stock is not stable due to inventory planning management did not account properly resulting erratic stock ( excess or reduced ) from the storehouses.Of problems that show above a solution that will be given is the manufacture of Supply Management Design Build Applications using Economic Order Quantity (EOQ) that can help companies to manage and determine the inventory with the calculation methods in the application, and that will be taken into consideration companies with the solutions presented by this application.From the test results the system is able to produce and provide some recommendations in the form of output that can assist companies in calculating the amount of data that must be ordered raw materials, the report items such as customer item, booking reports, sales reports and inventory planning report. Keywords : Application , Inventory Management , Economic Order Quantity.